SCAFFOLDING AS A LANGUANGE LEARNING TECHNIQUE FOR EARLY CHILDHOOD - Anisah, Zulfatun (Universitas Al-Hikmah Indonesia, 2024)
This study aims to explore the effectiveness of scaffolding as a language learning technique for early childhood education. Using a Systematic Literature Review (SLR) approach, the research analyzes 40 related articles to identify patterns, strategies, and supporting factors in the implementation of scaffolding. The results reveal that scaffolding significantly supports early childhood language development, particularly in phonology, grammar, and vocabulary. Three main patterns in scaffolding implementation were identified: breaking complex tasks into manageable steps, using interactive dialogues to model correct language, and providing real-time corrective feedback. Approximately 85% of the analyzed studies reported significant improvements in children’s language abilities through this technique. Furthermore, scaffolding has been proven effective in enhancing early literacy skills, such as reading and constructing word structures. However, the study also highlights challenges, such as the lack of training for educators and limited supporting resources. These findings emphasize the importance of professional training, the use of educational technology, and parental involvement to maximize scaffolding effectiveness. Grounded in Vygotsky's socio-cultural theory, scaffolding serves as a temporary support framework that enables children to reach their Zone of Proximal Development (ZPD). This study contributes to the literature on early childhood education by providing practical guidance and strategic recommendations for educators to effectively implement scaffolding.